Peranan Disperindag Kab. Malang terhadap Pemasaran dan Peningkatan Omset Batik Sengguruh - Hafidlotun Nadziroh; Desi Fitriya; Miftahul Ulum; R.M. Mahrus Alie (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
Creative economy-based Small and Medium Industries (SMEs) play a vital role in driving regional economic growth, job creation, and preserving local culture. However, batik SMEs still face various obstacles, such as limited market access, low digital technology utilization, and fluctuating sales turnover. This study aims to analyze the role of the Malang Regency Department of Industry and Trade (Disperindag) in increasing marketing reach and sales turnover for Sengguruh Batik SMEs. The study used a qualitative descriptive approach with data collection techniques through semi-structured interviews, observation, and documentation. Research informants included Sengguruh Batik owners and Malang Regency Department of Industry and Trade officials involved in SME development. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that Disperindag plays a role as a facilitator, regulator, and catalyst through training, digital marketing, exhibition facilitation, business legality assistance, promotion of superior regional products, and local batik shopping programs. The program expanded marketing reach through websites, e-catalogs, marketplaces, social media, and physical stores, and increased Batik Sengguruh's sales turnover from approximately IDR 20–30 million to IDR 30–50 million per month. These findings confirm that synergy between local governments and small and medium enterprises (SMEs) can increase the competitiveness of local culture-based businesses and serve as the basis for policy recommendations for strengthening SMEs focused on digital transformation and the sustainability of the creative economy.